PEMBERIAN REBUSAN DAUN SALAM TERHADAP PENURUNAN KADAR ASAM URAT PADA LANSIA : STUDI LITERATUR - Pulung Herdianto Pulung; Aida Khairunisa; Fitri Febriyanur (Poltekkes Kemenkes Aceh, 2023)
Gout is a disease due to abnormalities in purine metabolism, this can occur due to oversecretion of uric acid or decreased kidney function. The cause of high uric acid levels will cause an increase like a needle, especially in the joints which will cause pain. The purpose of this study was to determine the effect of giving bay leaf boiled water on decreasing uric acid levels in the elderly. The method uses a literature study approach. Search for articles using the Google Scholar database. The search results obtained 500 articles consisting of 475 research articles according to the selection of journals for the last 10 years, and 439 articles according to the selection of titles and duplicates. Of the 439 articles, 436 articles were published so that 3 articles were reviewed. The conclusions of the 3 journal articles explain the effect of giving bay leaf boiled water on reducing uric acid levels in the elderly. Shows that there is a difference between the mean value of uric acid levels before giving 7.26 mg/dl of bay leaf boiled water and after giving 2.75 mg/dl of bay leaf boiled water.